Achieving Ultrahigh‐Rate and High‐Safety Li+ Storage Based on Interconnected Tunnel Structure in Micro‐Size Niobium Tungsten Oxides. Issue 12 (19th February 2020) - Yang, Yang; Zhu, He; Xiao, Jinfei; Geng, Hongbo; Zhang, Yufei; Zhao, Jinbao; Li, Gen; Wang, Xun‐Li; Li, Cheng Chao; Liu, Qi
Abstract: Developing advanced high‐rate electrode materials has been a crucial aspect for next‐generation lithium ion batteries (LIBs). A conventional nanoarchitecturing strategy is suggested to improve the rate performance of materials but inevitably brings about compromise in volumetric energy density, cost, safety, and so on. Here, micro‐size Nb14 W3 O44 is synthesized as a durable high‐rate anode material based on a facile and scalable solution combustion method. Aberration‐corrected scanning transmission electron microscopy reveals the existence of open and interconnected tunnels in the highly crystalline Nb14 W3 O44, which ensures facile Li + diffusion even within micro‐size particles. In situ high‐energy synchrotron XRD and XANES combined with Raman spectroscopy and computational simulations clearly reveal a single‐phase solid‐solution reaction with reversible cationic redox process occurring in the NWO framework due to the low‐barrier Li + intercalation. Therefore, the micro‐size Nb14 W3 O44 exhibits durable and ultrahigh rate capability, i.e., ≈130 mAh g −1 at 10 C, after 4000 cycles. Most importantly, the micro‐size Nb14 W3 O44 anode proves its highest practical applicability by the fabrication of a full cell incorporating with a high‐safety LiFePO4 cathode. Such a battery shows a long calendar life of over 1000 cycles and an enhanced thermal stability, which is superior than the current commercial anodes such as Li4 Ti5 O12 . Abstract : Micro‐size Nb14 W3 O44 with interconnected tunnel structure is synthesized by a facile solution combustion method. Li + insertion/extraction in Nb14 W3 O44 is a single‐phase solid‐solution electrochemical mechanism, leading to high Li + diffusion coefficient and excellent structural stability during cycling. The as‐prepared Nb14 W3 O44 exhibits ultrahigh‐rate and high‐safety Li + storage performance.